THE EFFECT OF PREVIEW, QUESTION, READ, REFLECT, RECITE & REVIEW (PQ4R) STRATEGY ON STUDENTS’ READING COMPREHENSION ABILITY ON NARRATIVE TEXT OF THE SECOND YEAR STUDENTS’ OF SMPN 11 PEKANBARU - Nadya Putri Gustryana; Atni Prawati; Desri Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The objective of this research was to find out the effect by using PQ4R Strategy in teaching reading. PQ4R Strategy is one of the strategies proposed to be a good strategy in improving the students’ reading comprehension. PQ4R consists of a six-step process involves previewing, questioning, reading, reflecting, reciting & reviewing. This research is an experimental research focused on quantitative approach. There are two variables: Independent and dependent variable. The independent variable is using PQ4R strategy and dependent variable is the students’ reading comprehension. The population of this research was the second year students of SMPN 11 Pekanbaru and the writer choose 8.6. They were 40 students. The writer used reading comprehension test items inform of multiple choice as the instrument for the measurement of comprehension achieved by the students after applying PQ4R Strategy. The obtained data were analyzed by using SPSS version 16.0. The result of the data showed that from 40 students. It was found out that in PQ4R Strategy there are 34 srudents (85%) who belong to the excellent category and 6 students (15%) who belong good category. In other words, the researcher can said that the Reading Comprehension of second year students of SMPN 11 Pekanbaru was in Excellent Category.Key words : Testing, Reading Comprehension, PQ4R Strategy